Digital Marketing Strategy Through Content Marketing and Influencer Collaboration: The Impact on Consumer Buying Interest CV Albaik Adem Sejahtera - Aisyah, Amanda Suci; Ambadar, Rizco Turino; Hariputra, Fikky Ardianta; Tatasari, Titis (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2025)
This research is important to carry out because there is still little research that discusses the impact of collaboration between content marketing and influencer marketing on consumer buying interest, especially in the small and medium enterprise (SME) sector such as CV Albaik Adem Sejahtera. This research method uses a quantitative descriptive approach with a literature review to analyze the impact of digital marketing strategies through collaboration between content marketing and influencers on consumer buying interest at CV Albaik Adem Sejahtera. This research aims to provide an in-depth overview of the synergy influence of content marketing and influencers in building consumer buying interest, by relying on relevant secondary data. The research results showed that A digital strategy that integrates content marketing and influencer marketing has proven effective in increasing consumer buying interest at CV Albaik Adem Sejahtera. This approach successfully increases brand awareness through relevant content promoted by credible influencers, while building emotional connections with consumers through educational and entertaining material. In addition, collaboration with influencers who are in line with brand values strengthens the company's positive image and increases consumer confidence in the product. The combination of consistent marketing content and authentic reviews from influencers significantly drives consumer buying interest. In conclusion, this strategy also contributes to increasing customer loyalty, creating consumers who not only buy the product but also recommend the brand to others, thereby strengthening business sustainability. Keywords: Digital Marketing; Influencer; Content Marketing